Library - use skills of new undergraduates and library orientation programme at University of Ibadan (2002)
Survey data were used to investigate the Library - use skills possessed by the new under- graduates of University of Ibadan before they gained admission into the institution. Five hundred copies of the questionnaire were administered to the newly set of students admit- ted for the 2000/2001 academic session. Analysis shows that most students lacked the basic library skills of catalogue use, locating Information by the aid of Classification number, and the use of Computer to acess information. The timing, the duration and the content of the library Orientation Programme are not well planned to make the Programme beneficiary to the students. The paper recommends aggressive instruction on library use that will be practical oriented to help the students acquire the lacked skills. More time should be given to the programme and it should be conducted at a period when most students would have completed their registration.